2014
DOI: 10.1007/s00380-014-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of arterial stiffness and cardiovascular hemodynamics by oscillometric method in psoriasis patients with normal cardiac functions

Abstract: Arterial stiffness is associated with increased cardiovascular risk. Pulse wave velocity (PWV) and augmentation index (AIx) are non-invasive markers for assessment of arterial stiffness. Increased arterial stiffness is associated with atherosclerosis in patients with psoriasis. Previous studies have shown that high neutrophil-to-lymphocyte ratio (NLR) predicts poor cardiovascular outcome. The aim of this study was to evaluate arterial stiffness and cardiovascular hemodynamics by oscillometric method in psorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
5
10
0
1
Order By: Relevance
“…Pulse wave velocity and augmentation index, non-invasive markers for assessment of arterial stiffness, were found to be significantly higher in patients with Ps [12].…”
Section: Discussionmentioning
confidence: 95%
“…Pulse wave velocity and augmentation index, non-invasive markers for assessment of arterial stiffness, were found to be significantly higher in patients with Ps [12].…”
Section: Discussionmentioning
confidence: 95%
“…Also, increased arterial stiffness was associated with atherosclerosis [24]. Previous reports found that BP variability was a significant indicator for arterial atherosclerosis and stiffness in patients at high risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…The initiation of atherosclerosis is characterized by activation of the vascular endothelium [23]. We previously reported that patients with psoriasis had reduced vascular function [24]. We used an oscillometric technique for the assessment of arterial stiffness parameters and cardiovascular hemodynamics in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%